Hukum Ekonomi Nasional dan Kemandirian Pesantren: Studi atas Prinsip Keadilan Sosial Pancasila - Yusuf Arbi; Fajrul Fithri; Achmad Dimas; Habib Zein; Ahmad Muhammad Mustain Nasoha (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
This study on National Economic Law and Pesantren Economic Independence: An Analysis of the Pancasila Principle of Social Justice arises from the need to examine how national economic regulations support the empowerment of pesantren as socio-economic institutions rooted in religious values. Pesantren hold strategic potential in strengthening community-based economic development, yet they often face structural and regulatory barriers that limit their competitiveness. This research aims to analyze the relationship between the Pancasila principle of social justice and the framework of national economic law in enhancing the economic independence of pesantren. Using a normative-juridical approach and qualitative analysis, this study reviews relevant legislation, academic literature, and economic practices implemented by pesantren across various regions. The findings indicate that the principle of social justice requires equitable distribution of economic resources and the empowerment of religious institutions as active economic actors. When implemented inclusively, national economic law can serve as a regulatory instrument that strengthens pesantren’s economic ecosystem through supportive policies, access to financing, and cross-sector collaboration. In conclusion, integrating Pancasila values into national economic law provides a normative foundation for establishing economically independent, equitable, and sustainable pesantren that contribute meaningfully to national economic development.